Factors influencing the use of intuition in strategic decision making - dahak, abdenour (Milev Journal of Research and Studies, 2018)
The process of decision-making in general and the process of strategic decision-making in particular worthy topics of research and study old and recent. It is also a complex and controversial subject between researchers and management. Several field studies on the role of intuition in the strategic decision-making process are still only slightly advanced and have several shortcomings in the methodological aspects, which are mainly the difficulty of measuring the intuition and the variety of methods and tools used in this regard. As for the study of the relationship between intuition and strategic decision, researchers who are interested in this, often suggest definitions of in-depth intuition. In recent years, however, a lot of research and studies have been conducted on the factors influencing the use of intuition in strategic decision-making.